Electrokinetic nanoparticle injection for remediating leaks in oil well cement. (15th December 2017) - Němeček, Jiří; Li, Linfei; Xi, Yunping
Highlights: Novel electro-kinetic injection of nanoparticles into hardened cement is used for remediation of leaks in oil well cement for the first time. The oil well cement is characterized with high porosity and severe damage in operation. Both is taken into account in the paper. Novel nanoparticles including anionic (nanosilica), cationic (nanoalumina) and hybrid (nanoalumina coated nanosilica) particles are tested in the paper. The mechanisms of agglomeration of nanoparticles in well cement were examined. Results are verified by combination of experimental techniques (SEM, BET, electrical measurements). Abstract: This paper presents experimental results on injecting nanoparticles into a hardened oil well cement with electromigration technique. Oil well cement is a special cement type used in underground constructions to protect steel casing of oil wells, CO 2 storage wells or oil and gas platforms. Due to the technological reasons, the hardened cement is characterized with a high initial porosity. Further distressing and fracturing occurs in the hardened cement originating from the harsh underground environment which includes elevated pressure and temperature. This leads to severe leakages of the stored media and puts the steel casing to the risk of corrosion. The paper proposes to use a non-destructive remediation technique for the cement repair based on the electrokinetic injection of nanoparticles into the pore and crack space in the material. It shows the efficiency of the technique and presents results from injections with a variety of differently sized nanosilica, microsilica and nanoalumina particles. Characterization of the treated samples was based on microscopy observations, electrical measurements, the change in their open porosity and nanopore surface area assessed by the BET technique. It was found that the electrokinetic process and driving of particles in samples is very efficient and reduces the sample porosity by about 4–7% with respect to the initial porosity of intact specimens and 5–8% on aged samples. The BET analysis confirmed reduction of the inner pore surface area in the treated samples. Increasing level of agglomeration of particles on the surface as well as in the inner pores was observed during electrokinetic treatment and documented with the electric current measurements.